On the efficiency of placement service and programme placement at the public employment offices in Sweden - Jan Johannesson (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
This paper is a summary of three implementation studies on the efficiency of job placement service and programme placement at public employment service offices in Sweden. By the research design 'Comparisons by pairs of offices under matched control of external independent variables' the studies aim to characterize good employment office management practices. The research design, the methods used and the results reached are presented and discussed. Specifically, the paper proposes that good office management practices are characterized by a high ability to give self-service and assistance to self-service, and to give priority to individualised service to employers. – – Dieser Bericht ist eine Zusammenfassung von drei Studien zur Effizienz der Arbeitsvermittlung und Programmteilnahme in identischen Arbeitsämtern. Durch die Untersuchungsmethode 'Paarweiser Vergleich von Arbeitsämtern mit gleichen äußeren Verhältnissen' wird ein Versuch gemacht, gute Verwaltungspraxis der Arbeitsämter zu charakterisieren. In diesem Bericht werden Untersuchungsmethode und Ergebnisse beschrieben und erörtert. Es zeigt sich, dass die Komponenten einer guten Verwaltungspraxis von hohem Maß aus einer guten Infrastruktur zur Selbstbedienung für Arbeitssuchende und individualisierten Diensten an Arbeitgebern bestehen.
Keywords: 330; Arbeitsvermittlung; Arbeitsmarktpolitik; Betriebsvergleich; Erfolgsfaktor; Schweden